2010
DOI: 10.1007/s10522-010-9310-7
|View full text |Cite
|
Sign up to set email alerts
|

The effect of dichloroacetate on health- and lifespan in C. elegans

Abstract: Aging is associated with increased vulnerability to chronic, degenerative diseases and death. Strategies for promoting healthspan without necessarily affecting lifespan or aging rate have gained much interest. The mitochondrial free radical theory of aging suggests that mitochondria and, in particular, age-dependent mitochondrial decline play a central role in aging, making compounds that affect mitochondrial function a possible strategy for the modulation of healthspan and possibly the aging rate. Here we tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 82 publications
2
48
0
Order By: Relevance
“…When we examined the level of ROS generation in DCA-exposed flies at different days of their life, we observed that prolonged exposure of DCA to Drosophila reduced the level of ROS generation with an advancement of their age. This is in agreement with a previous study wherein reduced ROS level was evident in DCA-exposed C. elegans (Schaffer et al 2011). Concurrent with reduced ROS level, a significantly higher GSH content was observed in DCA-exposed aged flies as evident by a negative correlation drawn between ROS and GSH content (Y ROS = −0.848 GSH +1.881, r=−0.966, P=0.0017) with respect to age.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…When we examined the level of ROS generation in DCA-exposed flies at different days of their life, we observed that prolonged exposure of DCA to Drosophila reduced the level of ROS generation with an advancement of their age. This is in agreement with a previous study wherein reduced ROS level was evident in DCA-exposed C. elegans (Schaffer et al 2011). Concurrent with reduced ROS level, a significantly higher GSH content was observed in DCA-exposed aged flies as evident by a negative correlation drawn between ROS and GSH content (Y ROS = −0.848 GSH +1.881, r=−0.966, P=0.0017) with respect to age.…”
Section: Discussionsupporting
confidence: 94%
“…In addition, modulated expression of hsps (hsp70, hsp27, and hsp22) has been reported to alter life span in flies (Kim et al 2010;Liao et al 2008;Tatar et al 1997) and higher level of HSPs is reported in longerlived mammals and birds (Salway et al 2011). In the same context, improved health-and life span were observed in DCA-exposed Caenorhabditis elegans (Schaffer et al 2011). However, studies regarding expression of hsps in DCA-exposed organisms are inadequate.…”
mentioning
confidence: 99%
“…Mitochondrial copy number was quantified according to (Schaffer et al, 2011). Briefly, individual worms were picked into PCR tubes, lysed, and mtDNA copy number of individual nematodes was determined by quantitative real‐time PCR (qRT‐PCR) as previously described (quantified by serial dilution) (Gruber et al, 2011; Schaffer et al, 2011).…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, it has been realized that the nutritional components, specially the sugars and metal-based micronutrients, can induce, enhance and amplify the molecular damage either independently or in combination with other inducers of damage (Schaffer et al 2011). Additionally, interest in the role of epigenetics as the molecular basis for age-related changes has resurged (Kahn and Fraga 2009).…”
Section: Molecular Basis Of Ageingmentioning
confidence: 99%